A epigrafia do Convento de S. Francisco de Lisboa : roteiro - Baeza, Blanca Alejandrina Abranches (2021)
This project results from the process of carrying out the inventory of the epigraphic heritage existing in the former Convento de S. Francisco de Lisboa and which today houses the a Faculdade de Belas Artes da Universidade de Lisboa (FBAUL), Faculty of Fine Arts of Lisbon. If we consider that the convent originated in the thirteenth century, it implies an interval of almost eight centuries of history. In these 800 years of history the building has, of course, gone through many situations that changed its structure, from fires to earthquakes. However, there are inscriptions that go from the Medieval Era to our Contemporary Era. In fact we studied and invented a total of 47 inscriptions. The focus of this investigation is on the inventory process, in other words, the main interest lies in the application of a working methodology that can achieve this goal effectively. To establish the field of work with some rigor we put, on the one hand, the historical information and, on the other, our own search and identification of the inscriptions. One can say objective and subjective aspects respectively. However, both necessary aspects, a moment devoted to searching, identifying, reading and their proper photographic record are then confronted with historical documents to objectively clarify our observation on the ground, thus reducing the possibility of error. Crossing aspects that allowed the completion and completion of inventory sheets. Our big goal. The journey through the building motivated another aspect that was also present in this project, although in a secondary way, perhaps the subject of another investigation. The description of a whole typography that we have been observing, information by text, by letters, by numbers that did not fit directly with our research, but which we also considered necessary to expose. We conclude with proposals for the exposure of this existing heritage in the building of FBAUL, since we verify in situ their complete ignorance on the part of the people who usually walk through the building. We believe that inventory can be a factor that changes this situation and allows its valuation and consequent preservation.